Case study of a critically ill person with COVID-19 on ECMO successfully treated with leronlimab - Elneil, Sohier (J Transl Autoimmun, 2021)
The number of confirmed cases of infection with SARS-CoV-2, the virus causing Coronavirus disease 2019 (COVID-19), continues to increase and is associated with substantial morbidity and mortality in virtually every country in the world. Although in the long-term mass vaccinations remains the most promising approach to control the pandemic, evidence suggests that new variants of the virus have emerged that may be able to evade the immune responses triggered by current vaccines. Therefore despite the recent approval of a number of SARS-CoV-2 vaccines there remains considerable urgency for effective treatments for COVID-19. Severe-to-critical COVID-19 has been shown to be associated with a dysregulated host immune response to SARS-CoV-2 with elevated levels of C–C chemokine receptor type 5 (CCR5) ligands including chemokine C–C ligands 3, 4, 5, as well as interleukins 6 and 10. Leronlimab, a CCR5-specific humanised IgG4 monoclonal antibody originally developed for the treatment of HIV has been studied for the treatment of COVID-19. In the TEMPEST trial which compared leronlimab to placebo in subjects with mild-to-moderate COVID-19, a post hoc analysis showed that leronlimab led to improvements from baseline in National Early Warning Score 2 (NEWS2) at Day 14 in the sub-set of people with more severe disease. Data has also been released on a further ongoing, randomized, placebo-controlled phase 3 registrational trial of leronlimab in 394 people with severe-to-critical COVID-19. The results show that Day 28 mortality was reduced (P ​= ​0.0319) in the subset of participants receiving leronlimab plus other pre-specified commonly used COVID-19 treatments including dexamethasone administered as part of their standard of care (SOC) compared to participants receiving placebo plus other pre-specified commonly used COVID-19 treatments including dexamethasone as part of their SOC. Several cases have recently been reported demonstrated that treatment with leronlimab restores immune function and achieves clinical improvement in people with critical COVID-19. Here we report on a further case of a critically ill person who was treated with leronlimab. This person had been on extracorporeal membrane oxygenation (ECMO) for an extended period of time before receiving 4 doses of leronlimab. The male subject received his first dose of leronlimab on Day 79 of hospitalization he was weaned off ECMO by Day 84 and discharged from the ECMO intensive care unit on Day 91.